Pengaruh Penerapan Digitalisasi Akuntansi Dan Penerapan SAK EMKM Terhadap Kualitas Laporan Keuangan Dengan Keputusan Manajerial Sebagai Variabel Moderasi: Survei Pada UMKM Bidang Kuliner di Surakarta - Rahmawati, Risma; Astuti , Dewi Saptantinah Puji (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the effect of accounting digitalization and the implementation of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) on the quality of financial statements, as well as to examine managerial decisions as a moderating variable in culinary MSMEs in Surakarta. High–quality financial statements are essential for MSMEs as a basis for decision-making, particularly in facing business competition and limited resources.This research employed a quantitative method with a survey approach. Primary data were collected through questionnaires distributed to culinary MSME owners in Surakarta, selected using accidental sampling techniques. Data were analyzed using multiple linear regression and moderation interaction tests with the help of SPSS software. The results show that the implementation of accounting digitalization and SAK EMKM has a positive and significant effect on the quality of financial statements. Furthermore, managerial decisions are proven to moderate the relationship between accounting digitalization, SAK EMKM, and the quality of financial statements. These findings emphasize the importance of applying digital accounting technology and appropriate accounting standards to improve the quality of financial reporting, while strengthening the role of managerial decisions in supporting the sustainability of culinary MSMEs.